9 - Penser l’incertain : une application de l’audiosociologie et du schéma audiosociologique - Nzinga, Palama Bongo (Africa Development, 2021)
Audiosociology (synthetic science) and Audiosociological patterns, as social analysis and systematization tools, herein applied to the central theme of the XIX Congress of AISLF i.e. ‘Thinking uncertainty’, are perfectly in tune with the new philosophy of education at the dawn of Boubacar Camara’s third millennium, in accomplishment of Michel Granger’s thought, in the furtherance and extension of the work of Jacques-Jean Fromont, following R. Fossaert’s recommendations to responsibly usher into the twenty-first Century, and especially in the wake of the seven complex lessons in education for the future by E. Morin, particularly with respect to the need to link up that which was severed. ‘Thinking uncertainty’ suggests to take a leap into the unknown, that ocean where certainties are intertwined with uncertainties.